Relevance of UP elements for three strong Bacillus subtilis phage φ29 promoters - Meijer, Wilfried J. J. (Oxford University Press, 2004)
Various Escherichia coli promoters contain, in addition to the classical –35 and –10 hexamers, a third recognition element, named the UP element. Located upstream of the –35 box, UP elements stimulate promoter activity by forming a docking site for the C-terminal domain of the RNA polymerase α subunit (αCTD). Accumulating genetic, biochemical and structural information has provided a detailed picture on the molecular mechanism underlying UP element-dependent promoter stimulation in E.coli. However, far less is known about functional UP elements of Bacillus subtilis promoters. Here we analyse the strong early σ(A)-RNA polymerase-dependent promoters C2, A2c and A2b of the lytic B.subtilis phage φ29. We demonstrate that the phage promoters contain functional UP elements although their contribution to promoter strength is very different. Moreover, we show that the UP element of the A2b promoter, being critical for its activity, is located further upstream of the –35 box than most E.coli UP elements. The importance of the UP elements for the phage promoters and how they relate to other UP elements are discussed.